Urban Foundry: A Purposeful Business Model - Beth Cummings (Teaching cases on Entrepreneurship and Innovation: Unexplored Topics and Contexts, 2024)
This case study describes the business model of Urban Foundry, an SME with B Corp registration and is positioned during the covid-19 pandemic. The case is focussed on encouraging students to analyse what makes a B Corp enterprise, the advantages of this type of business model and how this compares with corporate social responsibility and social enterprise. The students are posed with the task of imagining that they are the owner of Urban Foundry and that they need to justify to their stakeholders whether they should maintain the principles of their B Corp registration during the global pandemic. The case is designed to enable students to debate short over long term organisational aims, the importance of purpose and the types of organisations that are the future of our society. The case can be linked with classical economic theory, global agendas such as the SDGs, corporate social responsibility and the triple bottom line.